Study of prevalence of thyroid peroxidase antibodies in preterm deliveries and recurrent pregnancy loss - Chandaka, Harika; Thejaswini, Parlapalli; Piyusha, M.; Vineela, Myneedi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Evaluation of thyroid disorder in pregnancy is essential for maternal health, obstetrical outcome and neurodevelopment of the child. Euthyroid pregnant women having positive thyroid peroxidase antibodies have an elevated risk of miscarriage, premature birth, gestational hypertension, and intrauterine fetal demise. Thyroid autoimmunity (TAI) and subclinical hypothyroidism (SCH) have been connected with adverse outcomes in pregnancy and foetus. The present aim of the study was to estimate the prevalence of TPO antibodies in recurrent pregnancy losses, first trimester abortions and preterm deliveries. Methods: This was a hospital-based cross-sectional prevalence study conducted for 18 months. The study consists of 100 women who had preterm deliveries and miscarriages attending to department of obstetrics and gynaecology, Narayana medical college and hospital, Nellore, Andhra Pradesh. Results: In our study out of 100 cases, 11 had high thyroid peroxidase antibody (TPOAb) levels, of which 9 had preterm deliveries and 2 had miscarriages. Out of 100 cases 5 cases had elevated T3 levels, 6 cases had elevated T4 levels and 24 cases had elevated TSH levels. Conclusions: There was a statistically significant association of thyroid peroxidase antibodies (TPOAb) with T3, T4, and, TSH (P<0.05) and it leads to developing hypothyroidism during pregnancy. The presence of TPOAb in pregnant women significantly increases the risk of preterm delivery. The screening of TSH and thyroid peroxidase antibodies is essential during pregnancy to avoid complications. So, screening T3, T4, TSH and thyroid peroxidase antibodies are essential during pregnancy to avoid complications.